ANKLE-BRACHIAL INDEX, FASTING BLOOD GLUCOSE, AND BMI SCORES AS PREVENTION AND MANAGEMENT OF THE RISK OF DIABETES MELLITUS COMPLICATIONS - Mardika Sari, Puspita; Sucipto, Adi; Retnaningsih, Listyana Natalia; Widarti, Sulis Mukaryanah; Rohmawati, Dwi Asih; Nurdjanah, Siti; Kuncara, Akhmad Surya; Febiyanita, Anggun (Universitas Darussalam Gontor, 2024)
Background: Diabetes has become an important health problem in the world, with prevalence rates increasing throughout the world. Uncontrolled diabetes can have various negative impacts, mainly increasing risk of complications as well as neuropathy and circulation disorders, which can cause various health problems, including diabetic foot wounds and the risk of amputation. Controlling blood sugar levels is one strategy to prevent the risk of complications. Health screening and monitoring can help in preventing and managing complications of uncontrolled diabetes. Purpose: The aim of this study was to determine the ankle-brachial index (ABI), spontaneous blood sugar levels (GDS), and body mass index (BMI) scores to prevent complications risk of Diabetes Mellitus in people through a health screening program. Method: This research was a cross-sectional approach with an observational design. It was conducted in June 2023 at Posbindu Ngrame, Tamantirto subdistrict, Kasihan district, Bantul regency, Yogyakarta province. The number of respondents in the study were 75 people who were taken by accidental sampling technique. Instruments used for data collection includes ABI questionare, microtoice and body scale for measure IMT, and glucose meter for GDS. Results: This study showed that (90.7%) of respondents were female, in the elderly category (41.3%), had primary school education (40%), and were housewives (50.7%). GDS levels were mostly normal (78.7%), BMI category 1 (41.3%), and ABI values were normal category (89.3%). Conclusion: The description of the risks and complications of DM based on GDS and ABI values is mostly normal, while based on BMI values, most are in the 1st-degree obese category.